Teachers’ Attitudes in the the Workplace : Myth and/ or Reality ? - Bashar, Ahmed (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES)
The central line of argument is that if teachers are trained to handle their emotions ; and hence, their attitudes toward their constituencies1 and workplaces, they will be more efficient and satisfied job-wise. The current paper starts with surveying the nature of attitudes and seeks to link attitudes to other constructs such as affect, beliefs, behavior, cognition, and values. It is also within the scope of this paper to investigate the structure of attitudes and the extent whereto it can affect teachers’ perceptions of and responsiveness to their socio-professional environment. Finally, the analysis of the investigation on teachers’ attitudes toward their socio- professional environment is laid out.   إن مسار حجتنا الأساسي هو كما يلي إذا درب الأساتذةعلى التحكم في عواطفهم، و بالتالي في إتجاهاتهم/ مواقفهم تجاه دوائرهم   و أماكن عملهم، فإنهم سوف يصبحون أكثر نجاعة و رضا في عملهم. تعمل هذه الورقة على سبر أغوار الإتجاهات/المواقف و تسعى إلى ربط هذا المفهوم بمفاهيم ذات الصلة (الوجدان، الإعتقاد، السلوك، الإدراك، و القيم). تدخل في نطاق هذا البحث أيضا هياكل الإتجاهات/ المواقف و مدى تأيرها في مدارك الأساتذة و إستجابتهم لبيئتهم الإجتماعية-المهنية. في الأخير، نقدم تحليلا للإستبيان الخاص بإتجاهات/مواقف أساتذة التعليم المتوسط تجاه بيئتهم الإجتماعية-المهنية